RESISTING EPISTEMIC COLONIALISMS: INTERNET(S) RESEARCH OTHERWISE - Beatrys, Bya; Omapang, Aspen K.B.; Stevens, Nikko; Neves Barros, Thiane; Mota, Polinho (AoIR Selected Papers of Internet Research, 2026)
When approaching the internet, as subject or object, academics risk reinforcing colonial logics unless we acknowledge these histories and adapt our knowledge production accordingly. Yet, within academic institutions, Western values narrow the options for “valid” knowledge production - in a process recognized as “epistemic colonialism” (Fanon, 1963). In response to these histories and pressures, Black feminists, Indigenous scholars and activist-researchers have created a breadth of perspectives, theories, techniques, and methods to resist the hierarchical mandates within academia that fail to acknowledge other ways of knowing that doesn't fit the mold of hegemonic “scientific” perspectives. Our panel brings together individuals engaged in active resistance both within and beyond academia. We reflect on the theoretical grounding and lived experiences of those working in communities committed to grassroots epistemological approaches and methodological alternatives. Our discussion is shaped by expertise in Indigenous studies, militant/insurgent research, transgender data epistemologies, Latin American Black feminist perspectives, and citizen/grassroots science and data. Collectively, we argue that liberatory research must be informed by local contexts and grassroots perspectives, critically engaging with the power structures shaping knowledge production. We emphasize an approach that remains critically attentive to the power structures shaping our own knowledge-making practices. Our panel explores how scholarly work can serve as a practice of resistance, subversion, solidarity, and transformation - both within and beyond institutional settings. This strengthens and unites our collectives to ultimately: resist and dismantle the coloniality of internet infrastructure.